2013
DOI: 10.1007/s10608-013-9584-6
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Future Time Perspective Manipulation on Affect and Attentional Bias

Abstract: Socioemotional selectivity theory proposes that decreased future time perspective would lead to an emphasis on goals of well-being, with attentional preference for positive information. We developed a procedure to manipulate future time perspective, based on mental imagery, to experimentally investigate its effects on attention and affect. In experiment 1, we tested a new measure of future time perspective, the scrambled sentence test. In experiment 2, 41 undergraduates were randomly assigned to the imagery pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
14
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 38 publications
2
14
0
Order By: Relevance
“…Although age-related changes in time horizons are frequently theorized to cause the positivity effect, previous research either did not directly test this assumption or yielded unclear results (Demeyer & De Raedt, 2013, 2014; DeWall & Baumeister, 2007; Pruzan & Isaacowitz, 2006, but see Kellough & Knight, 2012). In two experiments we examined the effect of manipulating time horizons on emotional picture memory recall.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although age-related changes in time horizons are frequently theorized to cause the positivity effect, previous research either did not directly test this assumption or yielded unclear results (Demeyer & De Raedt, 2013, 2014; DeWall & Baumeister, 2007; Pruzan & Isaacowitz, 2006, but see Kellough & Knight, 2012). In two experiments we examined the effect of manipulating time horizons on emotional picture memory recall.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is not clear whether these manipulations affected positivity by changing time horizons. Similarly, another study attempted to manipulate time horizons by having participants think about events happening in the next two days versus in the next 10 years (Demeyer & De Raedt, 2014). Here, no effect was found on attentional biases.…”
mentioning
confidence: 99%
“…Holmes, Lang, Moulds, and Steel (2008) also found that a highly dysphoric group appeared to show less vivid positive prospective imagery than a low dysphoria group. In line with previous evidence regarding the relationship between prospective cognition and emotional well-being, research proposes that cognition with a future time perspective might influence cognitive bias information processing (see Demeyer & De Raedt, 2014 for a review). That is, future time perspective cognitions, related to specific goals and motivational preferences lead to a preference toward positive information and away from negative information (Carstensen & Mikels, 2005).…”
Section: Effects Of Prospective Cognition On Cognitive Bias Modificatmentioning
confidence: 57%
“…That is, future time perspective cognitions, related to specific goals and motivational preferences lead to a preference toward positive information and away from negative information (Carstensen & Mikels, 2005). Demeyer and De Raedt (2014) found limited evidence that a more expansive future time perspective was related to avoidance of negative information. Similarly, the Reconstructive Memory Model (RMM) and Valuation Model (VM) explain that repetitive practice of positive future-oriented scenarios (RMM) might promote attribution of lower risk estimates and allocation of processing resources to positive-oriented stimuli, which increases expectations for occurrence of the events one practice (VM) (Miloyan, Pachana, & Suddendorf, 2014).…”
Section: Effects Of Prospective Cognition On Cognitive Bias Modificatmentioning
confidence: 99%
See 1 more Smart Citation